1998
DOI: 10.1165/ajrcmb.18.1.2792
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Exposure to Pseudomonas aeruginosa Proteases Increases the Vulnerability of the Alveolar Epithelium to a Second Injury

Abstract: The alveolar epithelium is not injured by the apical application of moderate doses of Pseudomonas aeruginosa strains that produce protease. To determine the effect of Pseudomonas proteases on the basolateral surface of the alveolar epithelium, a series of experiments were done, in which P. aeruginosa strains that produce and do not produce proteases were administered intravenously. Subsequently, an innocuous dose of bacteria was instilled into the lungs of the rabbits. Although all the intravenous Pseudomonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…In this hypothesis, the worsening of the oxygenation was not related to alveolar flooding but to mismatched of V/Q. Our findings are consistent with previous results of others indicating that alveolar epithelium is more resistant than the lung endothelium to acute lung injury [ 31 - 33 ]. We have also previously shown in another model that this discrepancy between ALC and LLC could be related to the endothelial barrier [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this hypothesis, the worsening of the oxygenation was not related to alveolar flooding but to mismatched of V/Q. Our findings are consistent with previous results of others indicating that alveolar epithelium is more resistant than the lung endothelium to acute lung injury [ 31 - 33 ]. We have also previously shown in another model that this discrepancy between ALC and LLC could be related to the endothelial barrier [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…The following parameters were measured 4 hours post-instillation of bacteria in blood samples obtained through direct aortic catheterization of anesthetized rats from each group: leukocyte and platelet counts, prothrombin time, fibrinogen and thrombin-antithrombin (TAT) complex concentrations. Measurements of TAT complexes were used as markers of thrombin formation [ 33 ]. TAT complexes were also measured in BAL fluids.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, we have shown that a large amount of the P. aeruginosa bacteria instilled into the distal airspaces go through the distal lung epithelium come in contact with the lung endothelium before reaching the bloodstream and cause the development of pulmonary edema (41). We have also reported that the intravenous administration of P. aeruginosa resulted in an increase of the vulnerability of the alveolar capillary barrier to an exposure to a nontoxic inoculum of the same bacterium instilled into the distal airspace of the lung (40). This previously published study demonstrated how P. aeruginosa in the circulation could amplify the minor lung epithelial injury caused by bacteria that colonize the distal airways.…”
Section: Clinical Relevancementioning
confidence: 97%
“…Briefly, the endothelial cells were grown on 35-mm cell culture dishes to 50% 6,40) confluence. After serum starvation for 6 hours, the wild-type P. aeruginosa strain PAK (bacterial to bovine cell ratio: Endothelial cells were grown on collagen-coated glass coverslips to confluence.…”
Section: Rac1 and Rhoa Activation Assaysmentioning
confidence: 99%
See 1 more Smart Citation